Preferences and Barriers to Counseling for and Treatment of Intimate Partner Violence, Depression, Anxiety, and Posttraumatic Stress Disorder Among Postpartum Women: Study Protocol of the Cross-Sectional Study INVITE - Seefeld, Lara; Mojahed, Amera; Thiel, Freya; Schellong, Julia; Garthus-Niegel, Susan (Frontiers in Psychiatry, 2022)
The cross-sectional study INVITE (INtimate partner VIolence care and Treatment prEferences in postpartum women) aims to examine treatment and counselling preferences and barriers in relation to the experience of intimate partner violence (IPV), depression and anxiety, and (childbirth-related) post-traumatic stress disorder (PTSD) among postpartum women in Dresden, Germany. Currently, the INVITE study consists of an interim sample of N = 1,787 participants with n = 891 completed interviews. Recruitment is ongoing, targeting a community sample of at least N = 4,000 women who complete various quantitative questionnaires via telephone interviews at three to four months postpartum. The differences in rates of IPV, postpartum depression and anxiety, and/or (childbirth-related) PTSD as well as treatment and counselling preferences and barriers between affected and non-affected women will be assessed. Further, predisposing variables, past and present stress exposure, enabling resources, as well as past and present health will be examined as predictors of service preferences and barriers. In this study protocol, the theoretical background, methods, as well as preliminary results regarding sociodemographic characteristics and birth-related factors of the interim sample are presented and discussed in terms of their socio-political relevance. Simultaneously assessing IPV, postpartum depression and anxiety, and (childbirth-related) PTSD will facilitate exploring comorbidities and concomitant special needs of affected women. Results of the INVITE study will therefore set the ground for well-aimed development and improvement of treatment and counselling services for the respective target groups by informing health care professionals and policy makers about specific preferences and barriers to treatment. This will yield the possibility to tailor services to the needs of postpartum women.